Interventions in location specific technologies and material utilization through Women Technology Park in India. Issue 3 (December 2020) - Mahesh, V; Ramana Rao, P V; Rajasri Reddy, I; Kiran, K; Gobinath, R; Murthy, P
Abstract: For any developing country, rural infrastructure development and expanding farming and the non-farming economy will be the major area to look forward to inclusive growth. To eradicate poverty and to have holistic growth primary approach should be towards developing employment potential, creation of enterprises and livelihood enhancement in rural people through region-specific technologies using indigenously available resources. The establishment of Women Technology Park (WTP) proposed in this research work will lay emphasis on promoting appropriate technological inputs that may improve productivity. Also, the quality of farm and non-farm sectors will be enhanced with supreme livelihood options in tandem with skill enhancement and capacity building. They also promote developing management skills coupled with the entrepreneurial mindset and will enable them to introduce new and innovative technologies. This kind of parks will promote usage of indigenous resources with increased energy and ecosystem management. Hence, it is envisaged that this kind of establishments, if done such as "Technology parks" will help to create a concrete and also tangible socio-economic benefits to the rural society by provision of newer technological solutions, alternate training method implementation which will end up in unique skill development and also will increase the support rendered for their implementation. In this research work, authors considered four different location-specific techniques for interventions including weaving technology, metal art skill development, banana fiber extracting and usage, habitat and construction technology development. Through the establishment of WTP, these technologies were tested first, and the rural women were trained to sustain via usage of those technologies for their livelihood.